2019
DOI: 10.1039/c8ra04594a
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductivity of silver nanoparticle doped carbon nanofibres measured by CS-AFM

Abstract: In this work, a pioneering study on the electrical properties of composite carbon nanofibres (CNFs) using current-sensitive atomic force microscopy (CS-AFM) has been demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 48 publications
2
20
0
1
Order By: Relevance
“…Therefore, a small amount of Ag on CB did not affect the mixing process but enhanced the electrical conductivity of rubber composites filled with Ag/CB at 10 phr. These results agreed with Ali et al, who showed significant enhancement in the electrical conductivity of carbon nanofiber by incorporating silver nanoparticles 21 . However, at higher amounts of Ag/CB, electrical conductivity of the rubber composites significantly dropped due to the instability of physically mixed Ag/CB.…”
Section: Resultssupporting
confidence: 91%
“…Therefore, a small amount of Ag on CB did not affect the mixing process but enhanced the electrical conductivity of rubber composites filled with Ag/CB at 10 phr. These results agreed with Ali et al, who showed significant enhancement in the electrical conductivity of carbon nanofiber by incorporating silver nanoparticles 21 . However, at higher amounts of Ag/CB, electrical conductivity of the rubber composites significantly dropped due to the instability of physically mixed Ag/CB.…”
Section: Resultssupporting
confidence: 91%
“…First, the yeasts were seeded into the prepared medium, and cultured in a conical flask on a shaker at 28 °C and 200 rpm for 3 d. Then, the fermentation broths were collected and centrifuged to obtain the supernatants. The last step, silver nitrate solutions were then added into the obtained fermentation broths, and adjusted to a final concentration of 10 mM in a conical flask wrapped with tinfoil 26 . The color changes of the solutions were observed after 4 d culture at 28 °C in the dark 27 .…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the excellent optical properties, AgNPs have a very high electrical conductivity. In a study by Ali et al [ 57 ], the incorporation of AgNPs into polyacrylonitrile fibers to produce carbon nanofibers (CNFs) was found to be an effective means of improving the conductive performance of the CNFs. A concentration-dependent influence of AgNPs on the enhancement in the electrical properties of CNFs was observed.…”
Section: The Optical and Electrochemical Properties Of Metal Nanoparticlesmentioning
confidence: 99%